Modelling of Changes in Evapotranspiration for an Area in Peninsular Malaysia - Lee, Teang Shui; Mohamed Najim, Mohamed Mujithaba; Haque, Md. Aminul; Feng, Huang Yuk (Universiti Putra Malaysia Press, 2005)
A study was carried out to check the sensitivity of evapotranspiration estimation due to changes in climate. The study used 30 years of data from the meteorological station in the FELCRA paddy estate, Seberang Perak, Peninsular Malaysia. The effect of changes in the climatic variables, temperature, solar radiation, relative humidity and wind speed on evapotranspiration were analyzed. Results showed that the mean temperature, mean relative humidity, mean wind speed, and net global radiation have changed by + 0.182 oC, -0.73%, -0.0365 mis, and +0.146 MJ/m2 respectively per decade, while the short wave radiation received has decreased by 0.0037 MJ/m2 per decade. The statistical analysis of the evapotranspiration estimations using selected methods showed that the Penman-Monteith, Blaney-Criddle and Pan evaporation methods give similar estimations (P = 0.05) and are suitable for the study area. When changes to the present climate are imposed for future decades, the over-estimation rate is linear with the Blaney-Criddle and Penman methods whereas for the PenmanMonteith method it is exponential. The overall increment expected after 5 decades is 5.3% and 6.9% with Penman and Blaney-Criddle methods respectively. The Penman-Monteith shows a 74.4% increment in the evapotranspiration over the next five decades.